2016
DOI: 10.1021/acsami.6b07792
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Resistive Switching in High-Density Nanocapacitor Arrays Based on BiFeO3 Ultrathin Films and Ordered Pt Nanoelectrodes

Abstract: Ferroelectric resistive switching (RS), manifested as a switchable ferroelectric diode effect, was observed in well-ordered and high-density nanocapacitor arrays based on continuous BiFeO3 (BFO) ultrathin films and isolated Pt nanonelectrodes. The thickness of BFO films and the lateral dimension of Pt electrodes were aggressively scaled down to <10 nm and ∼60 nm, respectively, representing an ultrahigh ferroelectric memory density of ∼100 Gbit/inch(2). Moreover, the RS behavior in those nanocapacitors showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Furthermore, the RS behavior in the negative voltage region is more expressive than in the positive voltage region, due to the asymmetric interface1243. It is further observed that the switching from HRS to LRS occurred at threshold voltage of ±1 V, as expected in ferroelectric Schottky diodes44. The switching field (E s ) = 56 ± 6 kV/cm, corresponding to 1 V, is consistent with the coercive voltages for polarization switching (E c ) = 52 ± 1 kV/cm.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, the RS behavior in the negative voltage region is more expressive than in the positive voltage region, due to the asymmetric interface1243. It is further observed that the switching from HRS to LRS occurred at threshold voltage of ±1 V, as expected in ferroelectric Schottky diodes44. The switching field (E s ) = 56 ± 6 kV/cm, corresponding to 1 V, is consistent with the coercive voltages for polarization switching (E c ) = 52 ± 1 kV/cm.…”
Section: Resultssupporting
confidence: 77%
“…AAO boasts additional advantages such as large scale fabrication, and tunablility of the nanopore size, thickness and interpore spacing, motivating its use in recent studies of nanoscale memristors. [25][26][27][28] Figure 1 shows the templated-directed process developed for embedding ordered metal nanoisland (NI) arrays within the oxide layer of M-O-M structures. The process begins (Fig.…”
Section: Template-directed Nanoisland Embeddingmentioning
confidence: 99%
“…Nowadays, the mainstream Si-based FLASH memories are expected to run into physical limits of scaling in the near feature. As a prominent alternative, resistive switching memories have emerged and attracted great attention. In general, the resistive memory consists of two metallic electrodes separated by an insulator layer, which exhibits electrically switchable resistance state between a high (HRS) and a low (LRS) level in a nonvolatile fashion. On the basis of various materials and different mechanisms, many resistive devices have been proposed in the past decades, such as the resistance random access memories that are functioned by the formation/rupture of conductive filaments inside the insulators and the ferroelectric-resistive memories that are realized by the polarization modulation on the band alignment across the metal/ferroelectric/metal devices. An important feature of the resistive switching memories is the two-terminal structure, making the integration of them into passive crossbar array feasible. The resistive devices, therefore, have great potential to achieve fast write/read access, low power consumption, and, more importantly, high data-storage density with the cell size reduced to 4 F 2 ( F = minimum feature size).…”
Section: Introductionmentioning
confidence: 99%